1965
DOI: 10.1063/1.1714449
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in Gamma-Irradiated Silicon

Abstract: T~e l~fetimes of excess carriers in phosphorus-doped, float-zoned silicon were measured before and after lrradlatI~n by cobal~-60. gamma rays. Recombination in the samples prior to irradiation was dominated by a. donor-like recombmatIOn center located 0.13 eV above the valence band. After irradiation, two recombination centers were found in the samples: one located at E c-O.17 eV and the other at Ec-O.40 eV. The center at eV can be identified with the oxygen-vacancy defect (Si-A centel), but no positive ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Q = 10 to 1000 Qcm grown by the Czochralski (pulled) and vacuuxn floating-zone techniques were used. The samples 13 x 3 x 2 mm3 in size were irradiated (Tirr 30 "C) with y-rays of 6oCo (ye) or y-rays of the bremsstrahlung spectrum of electrons with energy E, = 100 MeV (yB).…”
Section: Methodsmentioning
confidence: 99%
“…Q = 10 to 1000 Qcm grown by the Czochralski (pulled) and vacuuxn floating-zone techniques were used. The samples 13 x 3 x 2 mm3 in size were irradiated (Tirr 30 "C) with y-rays of 6oCo (ye) or y-rays of the bremsstrahlung spectrum of electrons with energy E, = 100 MeV (yB).…”
Section: Methodsmentioning
confidence: 99%
“…Powders possess a lot of defects on the surface that trap charge carriers, and it has been widely believed that these defects work as electron–hole recombination centers. In fact, there are numerous reports that the lifetime of photogenerated charge carriers becomes shorter on introducing defects into a crystal. However, recently it was reported that photocarriers in defect-rich SrTiO 3 (STO) powder had longer lifetimes than those in defect-free SC STO, and defects can enhance the photocatalytic activities . These reports seem to contradict each other and imply that defects have properties of both accelerating and decelerating recombination.…”
Section: Introductionmentioning
confidence: 99%
“…i A-centre produced by joining of oxygen was found 0.17 eV below the conduction band (3). The impurity compensated depletion layer of the drift detector contains lithium atoms which a r e on interstitials.…”
mentioning
confidence: 93%